A specific UDP-glucosyltransferase catalyzes the formation of triptophenolide glucoside from Tripterygium wilfordii Hook. f. (October 2019) - Ma, Baowei; Liu, Xihong; Lu, Yun; Ma, Xiaochi; Wu, Xiaoyi; Wang, Xing; Jia, Meirong; Su, Ping; Tong, Yuru; Guan, Hongyu; Jiang, Zhouqian; Gao, Jie; et al.
Abstract: Tripterygium wilfordii Hook. f. is a perennial woody vine member of the Celastraceae family. As a traditional Chinese medicine, it contains complex chemical components and exerts various pharmacological activities. In the present study, we identified a glucosyltransferase, TwUGT1, that can catalyze the synthesis of an abietane-type diterpene glucoside, namely, triptophenolide14-O-beta-D-glucopyranoside, and investigated the pharmacological activity of triptophenolide glucoside in diverse cancer cells. Triptophenolide glucoside exhibited significant inhibitory effects on U87-MG, U251, C6, MCF-7, HeLa, K562, and RBL-2H3 cells as determined by pharmacological analysis. The triptophenolide glucoside content of T. wilfordii was analyzed using Agilent Technologies 6490 Triple Quad LC/MS. The glucosyltransferase TwUGT1 belongs to subfamily 88 and group E in family 1. Molecular docking and site-directed mutagenesis of TwUGT1 revealed that the His30, Asp132, Phe134, Thr154, Ala370, Leu376, Gly382, His387, Glu395 and Gln412 residues play crucial roles in the catalytic activity of triptophenolide 14-O-glucosyltransferase. In addition, TwUGT1 was also capable of glucosylating phenolic hydroxyl groups, such as those in liquiritigenin, pinocembrin, 4-methylumbelliferone, phloretin, and rhapontigenin. Graphical abstract: Image 1 Highlights: The specific triptophenolide glucosyltransferase belonged to subfamily 88 and group E in family 1. Triptophenolide 14-O-beta-D-glucopyranoside is an abietane-type diterpene glucoside, which was discovered in  T. wilfordii . Triptophenolide glucoside exhibited inhibitory effects toward U87-MG, U251, C6, MCF-7, HeLa, K562, and RBL-2H3 cells. The residues His30, Asp132, Phe134, Thr154, Ala370, Leu376, Gly382, His387, Glu395 and Gln412 of TwUGT1 are crucial roles.